Equity and law - Falcón y Tella, María José (Martinus Nijhoff Publishers, 2008)
Presents a study of the different types of equity throughout history and in the different legal systems; the concept, content, limits, functions and types of equity; and, the relationship between equity and related ideas, and equity in all the branches of the legal order.